Potential of on‐chip analysis and engineering techniques for extracellular vesicle bioproduction for therapeutics. Issue 1 (31st January 2022) - Piffoux, Max; Silva, Amanda K. A.; Gazeau, Florence; Salmon, Hugo
Abstract: The clinical interest around extracellular vesicles (EVs) started during the year 2000s, now leading to new clinical diagnostic and therapeutic strategies. Due to their outstanding properties as biogenic drug delivery systems and as alternatives to cell therapy, the need to produce EVs with sufficiently high yield and quality for clinical use expedited the development of analytical techniques and dedicated bioproduction methods. Though preclinical studies revealed the potential of EVs to become next generation subcellular therapies that could lead to major breakthroughs in current therapeutics possibilities, they remain complex objects on both a physicochemical and biological level. Here, we review the capacity of microfluidic technologies to match EV‐based therapeutics need for clinical translation via standardized and intensified bioproduction methods. Indeed, some of the current routine tools used in bioproduction are already achieved on chips such as micromixers or particle sorting and analysis using field flow fraction or nanoparticle tracking analyzer. Also, microfluidics communities have developed a wide set of new techniques to isolate and quantify EVs, but the few that are adopted in a bioproduction workflow are well‐established since the 1990s. We first review the different EV generation and loading methods embedded on chip. We focus on EVs preparation methods, from purification to in‐line separative techniques. We finally describe the on‐chip analytical tools to analyze physicochemistry and phenotypes of EVs. Abstract : As the interest for extracellular vesicles (EVs) based biotherapies is increasing due to promising results, the authors review here the current microfluidic technologies for (i) production and loading, (ii) preparation and (iii) analysis of EVs and discuss their potential to produce high yield and high quality therapeutics as well as to understand their physico‐chemical and biological complexity in a clinical context.